A comparison between diode laser 976 nm and conventional technique in treatment of gingival fibromatosis - Marhab, Esraa Ibrahim; Mahdi, Zainab F. (Iraqi Journal of Laser, 2026)
Background: Gingival fibromatosis (GF) is an expansion of the gingiva’s connective tissue. Appeared during the onset of teeth eruption and postponed it. In order to remove this fibromatosis, a scalpel, electrocautery, or laser surgery is recommended. The objective of the study: is to evaluate the efficacy of a diode laser (976 nm) and its comparative benefits in the management of gingival fibromatosis, as opposed to a scalpel.  Material and method: Forty patients who complained of functional and esthetical problems due to delayed eruption were divided into two groups, one for surgical treatment with conventional scalped and another one for surgical treatment with diode laser. Follow-up visits are scheduled on the third day of treatment, 1, 2, and 4th postoperatively.  Clinical assessment is done by monitoring intra-operative bleeding, pain through the first week of treatment, functional interference, and clinical healing in follow-up visits. Overall satisfaction for patients and their parents was taken at the end of the treatment visits. The t-test and the Chi-square test were utilized as statistical methodologies for conducting data analysis.  Results: No or self-limiting bleeding in the laser group, lesser pain, and function interference in the laser compared with the conventional scalped group. Better clinical healing with the laser group through the first 2 weeks than with the scalpel group; all in each group cases achieve excellent healing at the 4th week postoperatively. All patients and their parents are very well satisfied with the outcomes.  Conclusion: Diode laser is preferable in surgical conducting of gingival fibromatosis to minimize postoperative pain and discomfort, enhance healing, and, ultimately, premium outcome.